The articulation between the STS Approach and Environmental Education for the contextualization of Acoustics in Physics Teaching - Moraes, Roberto Barreto de; Vianna, Deise Miranda (Journal of physics. Conference series, 2024)
Noise pollution presents itself in an invisible, dangerous, and permanent way, with long-lasting consequences. Acoustic discomfort within the school environment affects not only human health but also the quality of verbal communication and student performance. An appropriate acoustic environment contributes to the improvement of the teaching and learning process in addition to enhancing the interpersonal relationships involved in the educational process. Moreover, it is important to introduce acoustics-related subjects, such as environmental noise, into high school science and physics syllabi. As urban noise is a global concern and scope, students may face the need to make decisions related to environmental practices in their future lives, such as those concerning comfortable sound levels. Articulating the STS Approach with Environmental Education, we seek to combine the interdisciplinary content of Acoustics with an environmental awareness that goes beyond mere conservationist reductionism. In addition to the mandatory curricular knowledge, STS Education adopts a scientific and technological education based on a social construction that is culturally and socially contextualized.